Graph contractions in vector-valued metric spaces and applications. (3rd April 2021) - Petruşel, Adrian; Petruşel, Gabriela; Yao, Jen-Chih
ABSTRACT: In this paper, we will present a study of the fixed point equation x = f ( x ), x ∈ X (where ( X, d ) is a generalized metric space in the sense that d ( x, y ) ∈ R + m and f : X → X is a graph contraction) by the following perspectives: existence, uniqueness, approximation, data dependence of the operator perturbation, well-posedness, and Ulam-Hyers stability. The non-self case is also discussed and some applications are given.